The Impact of Indoor Exposure to Fungi and Bacteria on the Risk of Sensitization and Asthma in Children - Cavaleiro Rufo, João (2017)
Aim: To characterize indoor air microbiological exposure in schools as a predictor of allergic sensitization and asthma in children.